Tephra Deposition and Bonding With Reactive Oxides Enhances Burial of Organic Carbon in the Bering Sea - Longman, Jack; Gernon, Thomas M.; Palmer, Martin R.; Manners, Hayley R.; Gernon, Thomas M.; 2 School of Ocean & Earth Science University of Southampton Southampton UK; Palmer, Martin R.; 2 School of Ocean & Earth Science University of Southampton Southampton UK; Manners, Hayley R.; 2 School of Ocean & Earth Science University of Southampton Southampton UK (Global Biogeochemical Cycles, 2021)
Preservation of organic carbon (OC) in marine sediments exerts a major control on the cycling of carbon in the Earth system. In these marine environments, OC preservation may be enhanced by diagenetic reactions in locations where deposition of fragmental volcanic material called tephra occurs. While the mechanisms by which this process occurs are well understood, site‐specific studies of this process are limited. Here, we report a study of sediments from the Bering Sea (IODP Site U1339D) to investigate the effects of marine tephra deposition on carbon cycling during the Pleistocene and Holocene. Our results suggest that tephra layers are loci of OC burial with distinct δ13C values, and that this process is primarily linked to bonding of OC with reactive metals, accounting for ∼80% of all OC within tephra layers. In addition, distribution of reactive metals from the tephra into non‐volcanic sediments above and below the tephra layers enhances OC preservation in these sediments, with ∼33% of OC bound to reactive phases. Importantly, OC‐Fe coupling is evident in sediments >700,000 years old. Thus, these interactions may help explain the observed preservation of OC in ancient marine sediments. Plain Language Summary: The burial of organic carbon (OC) in marine sediments is one of the major carbon sinks on Earth, meaning that it removes carbon dioxide from the ocean‐atmosphere system. However, the speed at which burial occurs varies across the globe, and is dependent on a range of factors, from the amount of nutrients in the water column, to the type of sediment. Despite evidence suggesting that when tephra is deposited to the seafloor carbon burial is enhanced, very little work has been done to investigate this process. We have therefore analyzed sediments from the Bering Sea, where volcanoes from the Aleutian Islands and Kamchatka regularly deposit tephra in the ocean. We found that OC burial is indeed associated with ash deposition, and importantly, that OC is preserved in the ash layers themselves. We show ...